Motoric Automatisms of the Maxillofacial Region: a Lecture - Konstantin B. Petrov; Natalya A. Ivonina; Tatiana V. Mitichkina (Вестник восстановительной медицины, 2022)
INTRODUCTION. Effective kinesitherapy of peripheral and central paralysis of the mimic, masticatory, lingual and pharyngeal muscles requires in-depth study of the features of the cooperative work of these muscles in the norm and in pathology. AIM. To acquaint rehabilitation specialists with motor automatisms of the brachiofacial area and show the principles of their practical use. MATERIAL AND METHODS. We studied more than 70 literature sources on involuntary activity of the maxillofacial region and adjacent regions muscles as well as we summarized our own experience in rehabilitation of patients with peripheral facial neuropathies and with bulbar and pseudobulbar syndromes RESULTS AND DISCUSSION. The study showed that the face, neck, and arm are involved in various mesencephalic-bulbar automatisms, both normal (ontogenetic and psychosomatic synkinesia, postural-ocular and postural-mandibular reflexes) and pathological (trunk eye-facial synkinesia, oral automatic reflexes), much more closely than other body parts. All of them, with the exception of facial hyperkinesias, may serve as a basis for optimizing kinesitherapy methods for movement disorders of the brachiofacial region. CONCLUSION. The face, neck, and hand are closely involved in a variety of stem and subcortical automatisms. The better the physical therapist is familiar with the features of the existing or potentially available to the patient reflex activity in the part of the body being rehabilitated, the more effective the rehabilitation treatment will be. The face, neck and arm are closely involved in a variety of stem and subcortical automorphisms. The better a doctor or an instructor in exercise therapy is acquainted with the reflex activity present or potentially available in the part of the body to be rehabilitated, the more effective the rehabilitation treatment will be.